Intellectual curiosity and the scientific revolution a global perspective - Huff, Toby E. (Cambridge University Press, 2011)
Seventeenth-century Europe witnessed an extraordinary flowering of discoveries and innovations. The economic implications are set out in the concluding epilogue. All these unique developments suggest why the West experienced a singular scientific and economic ascendancy of at least four centuries.